(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article describes a high level of polymorphism of mental disorders in patients who are resorting to preventive institutions in the body. According to the WHO, more than half of patients with moderate to severe somatic diseases have some kind of mental illness. High prevalence of somatic and mental disorders, chronic course, polyethiology, polymorphism make diabetes the most appropriate model for the study and systematization of mental disorders in somatic patients.